A STUDY ON PREFERRED INVESTMENT TOOLS AMONG SALARIED CLASS INVESTORS WITH REFERENCE TO DELHI - 1. Ekta Tyagi, 2. Dr. Gaurab Kumar Sharma (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Individuals who have savings engage in the activity of investing; that is, they make investments out of their savings, or, to put it another way, they invest their money. There are many other ways to invest, including banks, gold, real estate, and post services mutual funds. Investors invest their money with a variety of goals in mind, including stability in income, appreciation, security, and profit. Using a sample size of 200 salaried employees, the researcher conducted a survey in Delhi using a questionnaire to examine the various investment options and the criteria that were taken into consideration while choosing an investment. The study only included individuals who were salaried because the respondents were limited to those who received a fixed income as a wage. Due to factors including security, tax savings, retirement benefits, and a steady income stream, salaried employees' investment patterns differ from those of professionals and business owners. The current study uses a self-assessment test to determine which financial tools individual individuals prefer.